Effects of garlic and aspirin on some blood parameters of new zeland rabbits fed cholesterol rich ration - Zafer Durgun; Ercan Keskin; Nurcan Dönmez; Feyyaz Önder (Eurasian Journal of Veterinary Sciences)
In the study, the effects of aspirin and garlic powder supplementation on some haemotological parameters in hypercholesterolaemic rabbits were investigated.Although the plasma cholesterol level in the groups fed cholesterol -rich ration for 4 weeks significantly (p<0.05) increased as compared with the control group, the plasma cholesterol levels in the group supplemented with garlic powder was found to be significantly lower than in both the group received the cholesterol-rich ration alone and the group fed the ration with aspirin (p<0.05).The haematocrit levels and erythrocyte counts in the groups supplemented with garlic (%29.2, 3.57x106 respectively) and aspirin (%28.2, 3.4x106 respectively) were significantly lower as compared with the control group (%38.5, 4.82x106 respectively) and the group fed the cholesterol-rich ration alone (%40.4, 4.78x106 respectively) (p<0.05). Haemoglobine amount also was determined to be significantly lower in the rabbits received aspirin (8.84 g/dl) than those in the control group (10.76 g/ dl) and the group fed the cholesterof-rich ration alone (10.58 g/dl) (p<0.05).There were no significant differences between the leucocyte types in the all groups. ECG also showed no significant changes with any treatment.The data shows the haemodilution reflected by the decreases in the haemotocrit, haemoglobine and erythrocyte levels with aspirin and garlic powder supplementation. But to support the prevalanl popular belief in the efficacy of garlic in the management of cardiovascular disease risks, further studies including the b,ood volume, body fluid and urine amount determinations are needed on this subject.